Impacto das percepções de suporte organizacional e social no trabalho sobre o bem-estar no trabalho da Enfermagem - Alves, Priscila Castro (2011)
Well-being at work is based on the Positive Psychology and can be defined as a psychological state composed by positive affective attachments with work and with the organization. This study had as objective to investigate the impact of organizational and social support at work on the well-being at work. The sample was composed by 340 workers that answered valid scales to measure the constructs: perception of social support at work, job satisfaction, job involvement, affective organizational commitment and perception of organizational support. The data were analyzed using SPSS, 12nd version, in order to calculate descriptive statistics, index of reliability for the scales, means differences and multiple regression coefficients. The main results showed that PSO explained 29% of the organizational affective commitment and 21% of the job involvement; the instrumental PSST was identified as the main variable to explain satisfaction with the salary, the task and the promotions, with percents varying between 18 and 19%; and, finally, the informational PSST and the PSO explained 23% of the satisfaction with the leaders. So, greater explanation was due to PSO and instrumental PSST, suggesting that the hospital administration must plan strategies to offer material and managerial support, and to value the contribution of the Nursing professionals, keeping in mind that the level of well-being of the health teamwork can reflect on the quality of attendance to the patients of the university hospital.